The identity of the frog fly Caiusa coomani Séguy, 1948 (Diptera, Calliphoridae) - Rognes, Knut (Zootaxa, 2011)
The type material of the nominal species Caiusa coomani Séguy, 1948 (Diptera, Calliphoridae), now placed in Phumosia Robineau-Desvoidy, 1830, has been examined and a lectotype designated to fix the interpretation of the name. In Hong Kong the larval stages of the species is a predator on the egg masses in foam nests of the brown tree frog Polypedates megacephalus Hallowell, 1861 (Anura, Rhacophoridae). Phumosia coomani is known from China, Japan and Vietnam. Discrepancies between the figured genitalia and the external features in Chinese reference works are pointed out.